1994
DOI: 10.1080/03079459408418973
|View full text |Cite
|
Sign up to set email alerts
|

Variations of clinical biochemical parameters of laying hens and broiler chickens fed aflatoxin‐containing feed

Abstract: SUMMARYTwo groups of 32 laying hens (Hyssex Brown) and two groups of 32 23-day-old (Hybro) broiler chickens were fed 2.5 and 5 parts/10 6 of aflatoxin in their diet for 4, 8, 16 and 32 days; 16 hens and 32 chicks were maintained as control groups (0 parts/10 6 ). After the intoxication period, a clearance period was established of 1, 2, 4 and 8 days. Relative weights of liver and kidneys significantly increased in intoxicated hens, but not in broiler chickens. Histological lesions in both types of bird consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
32
0
6

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 30 publications
5
32
0
6
Order By: Relevance
“…In addition, the obtained AST and CK values of both evaluated groups were higher than those reported by Dickel (1992), 222 U/L for broilers with ascites, and those of Fernandez et al (1994), of 198-225 U/L in layer hens fed a diet contaminated with aflatoxin.…”
Section: Evaluation Of Physiological Parameters Of Broilers With Dorsmentioning
confidence: 38%
“…In addition, the obtained AST and CK values of both evaluated groups were higher than those reported by Dickel (1992), 222 U/L for broilers with ascites, and those of Fernandez et al (1994), of 198-225 U/L in layer hens fed a diet contaminated with aflatoxin.…”
Section: Evaluation Of Physiological Parameters Of Broilers With Dorsmentioning
confidence: 38%
“…1). Os níveis séricos da AST, determinados neste trabalho, foram inferiores aos encontrados por Giroir et al (1991) e semelhantes aos encontrados por Saukas et al (1994), Fernandez et al (1994 e Krasnodebska-Depta e Koncicki (1999), que também não observaram efeito da idade sobre a variação dos níveis dessa enzima.…”
unclassified
“…Os valores de LDH foram inferiores aos apresentados por Saukas et al (1994) e similares aos encontrados por Fernandez et al (1994) e Krasnodebska-Depta e Koncicki (1999) aos sete, 14 e 21 dias de idade das aves. Há grande concentração nas hemácias dessa enzima, por essa razão, resultados diferentes entre autores podem estar relacionados à presença de hemólise, mesmo em pequenas quantidades no soro das aves (Kramer, 1989 (1994) e por Fernandez et al (1994), em aves clinicamente saudáveis.…”
unclassified
See 1 more Smart Citation
“…Rao &Joshi (1993) included 1.25, 2.50, 5 and 10ppm aflatoxin B 1 in layer rations for four weeks and found decreased egg production in birds receiving 5 and 10ppm of aflatoxin B 1 . Fernandez et al (1994) reported a significant reduction in egg production and oral lesions in layer chicken treated with 120ppb onwards for varying periods. Azzam & Gabal, (1998) reported a significant reduction in egg production of commercial layers fed with high levels of aflatoxin for six weeks.…”
Section: Aflatoxicosis In Commercial Layersmentioning
confidence: 99%